Policy drivers of China's integrated energy services: a current status review - Xiangyu, Xu; Zainordin, Nazatul Syadia; Sharaai, Amir Hamzah; Nik Ab, Nik Nor Rahimah (Malaysian Institute Of Planners, 2024)
Conventional energy production and consumption patterns seriously restrict global sustainable development. In the energy transformation process, integrated energy services play a key role in integrating clean energy and renewing energy consumption patterns. The European Union, the United States, and Japan are leading in developing policy frameworks and integrating integrated energy services. This paper compares and analyzes how the European Union, the United States, Japan, and China respond to the challenges of energy transformation through different energy policy systems. The energy policy systems of the European Union, the United States, and Japan are discussed for reference by China. The review reveals that (1) assigning tasks based on the energy transformation strength of each region is conducive to accelerating the speed of carbon emission reduction in each region; (2) continuous government support and targeted incentives are conducive to attracting market capital, thereby stimulating the advancement of energy technology; and (3) formulating energy efficiency standards for basic equipment can lay a good foundation for energy transformation.